2007
DOI: 10.4049/jimmunol.179.4.2330
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Bcl-2 through ERK Phosphorylation Is Associated with Human Macrophage Survival in an Estrogen Microenvironment

Abstract: Estrogen is a known immunomodulator with pleiotropic effects on macrophage function that partly accounts for the gender bias observed in numerous autoimmune, cardiovascular, and neurodegenerative disorders. The effect of estrogen on the survival of human macrophages is largely unknown, and in this study we demonstrate that 17β-estradiol (E2) provokes a death response in human THP-1 macrophages by initiating Bax translocation from cytosol to the mitochondria; however, a concomitant up-regulation of Bcl-2 create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 57 publications
1
54
0
Order By: Relevance
“…Although the Fas-mediated apoptosis after c-FLIP siRNA inhibition in B16 cells showed no difference compared with control siRNA, we cannot exclude that c-FLIP plays a role in the Fas resistance of B16 cells, because the effect of c-FLIP knock down is mild, and the expression of c-FLIP decreases only ∼50%. It was reported that activation of the ERK pathway and subsequent induction of antiapoptotic proteins, such as Bcl-2, play important roles in the survival of CD8 + T and NK cells (44,45) In B16 tumor cells stimulated by FasL + EXO, we found that Bcl-2 was upregulated after EXO stimulation, and specific inhibitors of ERK and NF-kB activation could decrease the expression of Bcl-2. But there was no increasing apoptosis in the B16 cells treated with Bcl-2 inhibitor compared with the group treated with DMSO or control, which suggests that Bcl-2 may not be involved in the Fas resistance of B16 tumor cells induced by FasL-expressed EXO (data not shown).…”
Section: Discussionmentioning
confidence: 64%
“…Although the Fas-mediated apoptosis after c-FLIP siRNA inhibition in B16 cells showed no difference compared with control siRNA, we cannot exclude that c-FLIP plays a role in the Fas resistance of B16 cells, because the effect of c-FLIP knock down is mild, and the expression of c-FLIP decreases only ∼50%. It was reported that activation of the ERK pathway and subsequent induction of antiapoptotic proteins, such as Bcl-2, play important roles in the survival of CD8 + T and NK cells (44,45) In B16 tumor cells stimulated by FasL + EXO, we found that Bcl-2 was upregulated after EXO stimulation, and specific inhibitors of ERK and NF-kB activation could decrease the expression of Bcl-2. But there was no increasing apoptosis in the B16 cells treated with Bcl-2 inhibitor compared with the group treated with DMSO or control, which suggests that Bcl-2 may not be involved in the Fas resistance of B16 tumor cells induced by FasL-expressed EXO (data not shown).…”
Section: Discussionmentioning
confidence: 64%
“…The homogenate was centrifuged at 1,300 Â g to isolate the nuclear fraction followed by centrifugation at 17,000 Â g in Optima XL-100K (Beckman Coulter) to isolate the mitochondrial fraction. Postmitochondrial supernatant centrifuged at 100,000 Â g provided the cytosolic fraction (23).…”
Section: Subcellular Fractionationmentioning
confidence: 99%
“…N-TER TM Nanoparticle siRNA Transfection System (SigmaAldrich, N2913) was used to transfect both macrophage-like THP-1 cells and HsMDMs as reported earlier. 52 …”
Section: Mirna Transfectionmentioning
confidence: 99%
“…Images were captured at 63x magnification using a Leica TCS SP5 II (Leica Microsystems, Wetzlar, Germany) confocal microscope and were processed for algorithmic quantification of LC3-II puncta using custom-written ImageJ macro-containing plug-ins as described previously. 52 At least 100 cells per condition were counted.…”
Section: Confocal Microscopymentioning
confidence: 99%